Turkmenistan - Russia: partner or competitor - Aleksandr Igorevich Morozov (Проблемы постсоветского пространства, 2017)
This article analyzes the relationship between the Russian Federation and Turkmenistan in the context of diversification of natural gas in the world market of hydrocarbons. Special attention was given the Turkmenistan gas pipelines which could affect the economic stability of Russia.